Perancangan Proses Bisnis Layanan Kartu Tanda Penduduk Elektronik (E-KTP) Berbasis Aplikasi Menggunakan TOGAF ADM - Muhammad Hanif Hasanain; Herman Tolle; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Department of Population and Civil Registration (DISPENDUKCAPIL) Malang city is an agency in charge of data collection and registration on matters related to population administration. However, since the pandemic, population services are expected to be based online in performing their services in accordance with government policies to reduce face-to-face. Therefore, it is necessary to design new business processes in order to facilitate the community in carrying out the process of population administration services. The design of this business process uses TOGAF ADM method by performing several stages, such as preliminary phase, architecture vision, requirement management, business architecture phase and simulation result comparison to see the improvement in time analysis to the defined business process model. Then obtained the results of the comparison calculation to see the difference in the time of the as-is business process model with to-be on each service that is, 1 day 10 hours 23 minutes 30 seconds for e-KTP creation service, 17 hours 6 minutes for e-KTP data change, 2 days 6 hours 45 minutes for making lost e-KTP, 1 day 12 hours 45 minutes for family card making, 1 day 20 hours 11 minutes 38 seconds for family card data change and 1 day 18 hours 31 minutes 38 seconds for family card creation is lost.